"Double Barrel" Lymphaticovenous Anastomosis: A Useful Addition to a Supermicrosurgeon's Repertoire. Issue 4 (19th April 2022) - Masoodi, Zulqarnain; Steinbacher, Johannes; Tinhofer, Ines E.; Czedik-Eysenberg, Manon; Mohos, Balazs; Roka-Palkovits, Julia; Huettinger, Nina; Meng, Stefan; Tzou, Chieh-Han John
Abstract : Background: Microsurgical amelioration of lymphedema has gained much traction in recent years and is now an established modality of treatment for this condition. Despite the development of many newer techniques, lymphaticovenous anastomosis still remains the most frequently carried out microsurgical procedure for lymphedema. One of the most common hurdles faced by lymphatic surgeons while carrying out a lymphaticovenous anastomosis is a mismatch in sizes of the vein and the lymphatic vessels. Method: This article describes a novel but simple "double barrel" technique, developed by the authors for carrying out lymphaticovenous anastomosis in cases of such lymphaticovenous mismatch. Seventeen double barrel anastomoses were carried out in 12 lymphedema patients, over a 4-year period from 2017 to 2021. Results: The overall success rate was 100%, as measured by clinical observation (venous washout, lymphatic backflow), the Acland vessel strip test, and by means of intraoperative ICG lymphography. Mild leakage was observed in four cases after release of the venous clamp and was corrected by application of additional sutures. Conclusions: The double barrel technique is a safe and effective tool that can be employed to deal with the bane of size mismatch, a persistent problem faced by lymphedema surgeons universally. Although we do not advocate it as a total replacement for other techniques, it can be a worthy addition to the present set of available options. In specific scenarios of mismatch with additional challenges, the double barrel technique has the potential to be considered as primus inter pares .